MOTIA Urdu ka guldasta Motia - Fozia Ehsaan farooq; Fozia Ehsaan Farooq (Lahore Oxford university press, 2024)
Urdu Ka Guldasta is a series of books for levels from pre-primary to eight that has enriched the minds of teachers and students alike.